Work Motivation in Geriatric Care: How Specific Factors Influence The Work Motivation of Geriatric Care Professionals - Goldschmidt, Toni (2012)
Work motivation is one of the most researched topics in organisational behavioural studies and widely used by businesses to increase employee motivation. Despite its popularity, motivational literature is basically non-existent for the increasingly important sector of geriatric care. It is therefore the objective of this paper to present an insight of the work motivation in geriatric care. Therefore, 20 geriatric care professionals participated in semi-structured interviews and the gathered data was subsequently connected to existing motivational literature. Consequently, interesting findings were revealed, showing the unique aspects of motivation in geriatric care. Practical implications were suggested to incorporate these aspects into managerial practice in order to increase motivation and the quality of work. Additionally, unexpected factors emerged emphasising the necessity for further research.